The rise of Asian elephants and tigers: what makes Indian and Chinese firms competitive?. Issue 2 (21st March 2019) - Berning, Sue Claire
Abstract : Purpose: The purpose of this study is to critically analyze the resources and determinants of capabilities and attributes which enable Indian and Chinese firms to develop competitive advantages. The leading research question asks whether the traditional concept of competitiveness can capture Indian and Chinese firms' competitiveness. Design/methodology/approach: A systematic and comprehensive literature review of 62 studies published between 1994 and 2016 with focus on Indian and Chinese firms is conducted to examine the nature and contextual conditions of their competitiveness, as well as the research methods and underlying theories. Findings: Turning disadvantages into advantages and shifting the points of take-off are the most outstanding findings. Moreover, the majority of 88 per cent of the examined studies concludes that Indian and Chinese firms built nontraditional competitive strengths. Research limitations/implications: Because of the unconventional competitiveness of Indian and Chinese firms, existing theoretical perspectives and research settings need revisions and extensions. Originality/value: Unlike most extant research on India and China, which studies country- or industry-level variables using aggregate data, this paper reveals distinct patterns and similarities and differences of firm-level characteristics. In addition, by exclusively focusing on Indian and Chinese firms' competitiveness, conclusions about their uniqueness and generalizability can be drawn.